The Unlearning: Deconstructing Fear and Insecurities - Desjarlais, Amy (Ars Medica, 2015)
In my dream, I saw my uncle’s house. My parents used to visit my uncle often and we’d go to his house. It was old, dank, and never seemed to have any light inside. I was always afraid when I had to go to this place. During my first visit to Dreamer’s Rock, the memory of this place came to me. In my dream I had sketched this house many, many times. I saw dozens of sketches. When I told my teacher what I saw, she asked me what I thought it meant. I told her. “It is my home, inside. It is how I feel about my own sense of security and love.” She nodded in agreement.